Continuing Professional Development (CPD) Model for Vocational High School Teachers in Indonesia (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The demand for higher-quality teaching and learning has become an important necessity in recent years. In line with this, several countries are focusing on Continuing Professional Development (CPD) to improve teacher competence as a strategy that can facilitate the acquisition of new types of knowledge and skills. The aim is to meet the contemporary needs of one of the existing education systems. However, the effective CPD model is still a matter of debate. Therefore, this study aims to develop a CPD model for Vocational High School (VHS) teachers. This study uses Research and Development (R&D) to develop a CPD model for VHS teachers. The results of the study indicate that the CPD model for VHS teachers has four model components consisting of (a) components of the teacher study group; (b) the teacher performance evaluation component; (c) teacher learning component; and (d) the teacher professional portfolio component. The four components can be integrated and can be implemented independently according to the needs of the teacher. This study has implications for several vocational education practitioners in developing the CPD program in vocational high school. This model can be used to reflect teachers, both individually and collectively, to improve teacher competence and performance.